Answer:
1 -> f
2 -> a
3 -> d
4 -> b
5 -> e
6 -> c
Step-by-step explanation:
We are given:
h(x) = 2 - 2x and g(x) = -2^x+2
a) k(x)= (g-h)(x) = g(x) - h(x)
= -2^x+2 - (2 - 2x)
= -2^x+2 - 2 + 2x
= -2^x+2x or 2x-2^x
k(x) = 2x-2^x = (g-h)(x)
So, 2 matches with a
b) k(x)= (g+h)(x) = g(x) + h(x)
= -2^x+2 + (2 - 2x)
= -2^x+2 + 2 - 2x
= -2^x+4-2x or 4 - 2^x -2x
So, k(x) = 4 - 2^x -2x = (g+h)(x)
So, 4 matches with b
c) k(x)= (2h - 2g)(x) = 2h(x) - 2g(x)
= 2(2 - 2x)-2(-2^x+2)
= 4 - 4x+2.2^x-4
= -4x+2^x+1 or 2^x+1-4x
So, k(x) = 2^x+1-4x = (2h - 2g)(x)
So, 6 matches with c
d) k(x) = (h-2g)(x) = h(x) - 2g(x)
= (2 - 2x)-2(-2^x+2)
= 2 - 2x+2.2^x-4
= -2-2x+2^x+1
= 2^x+1-2x-2
So, k(x) = 2^x+1-2x-2 = (h-2g)(x)
So, 3 matches with d
e) k(x) = (h-g)(x) = h(x) - g(x)
= (2 - 2x)-(-2^x+2)
= 2 - 2x+2^x-2
= -2x+2^x or 2^x-2x
So, k(x) = 2^x-2x = (h-g)(x)
So, 5 matches with e
f) k(x) = (2g+h)(x) = 2g(x)+h(x)
= 2(-2^x+2) + (2 - 2x)
= -2.2^x+4 + 2 - 2x
= -2^x+1+6-2x or 6 - 2^x+1-2x
So, k(x) = 6 - 2^x+1-2x = (2g+h)(x)
So, 1 matches with f